Analysis of validity and reliability of English formative tests - Sugianto, Aris (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2011)
This study was conducted in order to analyze the English formative tests made by the English teacher of grade VIII of SMPN-4 Mentaya Hulu based on the characteristics of a good test. The indicators to be analyzed were validity and reliability of the test. The validity covered the content and construct validity. The writer applied descriptive method in conducting this study. The population and sample of this study was the English teacher-made tests for the grade VIII of SMPN-4 Mentaya Hulu in the first semester of academic year 2008/2009. The writer analyzed 2 English formative tests as the representative of all English formative tests in the first semester of academic year 2008/2009. Based on the result of the data analysis, the writer found that the English formative test conducted on October 2008 belongs to high validity in its content validity and excellent validity in its construct validity. The English formative test conducted on November 2008 belongs to low validity in its content validity and high validity in its construct validity. While the English formative test both conducted on October 2008 and November 2008 are unreliable.